2021
DOI: 10.3389/fphar.2021.715354
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Modulates TLR4/Myd88/NF-Kβ Signaling Pathway in a Dose-Dependent Manner With Suppression of Oxidative Stress and Inflammation in an Experimental Model of Depression

Abstract: Depression is a common mental illness leading to upset or anxiety, with a high incidence rate in the world. Depression can lead to suicidal thoughts and behavior. The present study aimed to evaluate the effect of the direct oral anticoagulant rivaroxaban (RVX), in the model of depression induced by chronic unpredicted mild stress (CUMS) in rats. Fifty-six male Wister rats were randomly divided into seven experimental groups (8 rats/group); Group 1: Control group given vehicle per oral (p.o.), Group 2: RVXL-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…TLR4 signaling plays a pivotal role in stress‐induced neuroinflammation and MDD 53,54 . NF‐κB, a critical molecule downstream of PI3K/Akt signaling, regulates the secretion of multiple cytokines 55 and acts as part of the TLR4 downstream signaling pathway 56 . In our study, miR‐144‐5p restoration alleviated behavioral dysfunctions in CUS mice, and this effect was accompanied with decreased levels of PTEN and TLR4.…”
Section: Discussionsupporting
confidence: 54%
“…TLR4 signaling plays a pivotal role in stress‐induced neuroinflammation and MDD 53,54 . NF‐κB, a critical molecule downstream of PI3K/Akt signaling, regulates the secretion of multiple cytokines 55 and acts as part of the TLR4 downstream signaling pathway 56 . In our study, miR‐144‐5p restoration alleviated behavioral dysfunctions in CUS mice, and this effect was accompanied with decreased levels of PTEN and TLR4.…”
Section: Discussionsupporting
confidence: 54%
“…SOD is an antioxidant enzyme that scavenges superoxide anion free radicals and protects cells from damage caused by oxygen free radicals. MDA is a product formed by the reaction between lipids and oxygen free radicals, and its content represents the degree of lipid peroxidation ( Abdelzaher et al, 2021 ). In the current study, we used frozen sections to detect the level of ROS in mouse lung tissue, flow cytometry to detect ROS content, and ELISA to detect the levels of SOD and MDA; we found that IMD could inhibit the oxidative stress in VILI.…”
Section: Discussionmentioning
confidence: 99%
“…30 Oxidative stress stimulates numerous intracellular signaling pathways and causes the production of pro-inflammatory cytokines. 31 It is known that the brain is more vulnerable to oxidative stress than any other organ because of its higher oxygen consumption, higher lipid content and weaker antioxidant defense. 32 When cells are exposed to oxidative stress, NF-κB can be activated and phosphorylated into the nucleus, and then up-regulate pro-inflammatory cytokines such as TNF-α.…”
Section: Food and Function Papermentioning
confidence: 99%